Analisis Kesepadanan Terjemahan Teks Pendek Bahasa Mandarin - Lestari, Azizah Utami; Nadhifa, Raray Fairuz; Wikarti, Aprilia Ruby; Trihardini, Ayu (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2023)
Foreign language learning is inseparable from translation activities. Translation activities are carried out in the Mandarin skills course at Jakarta University Mandarin Education Study Program. In order to translate from the source language (SL) to target language (TL) and produce an equivalent translation, apart from the need for proper techniques and methods, it is also necessary for translators to understand the type of text and the type of meaning. The aim of this study is to describe the equivalence of translation of 1 selected text translated by 10 students of 6th semester PSPBM UNJ, using the theory of equivalence of traslation by Baker. This study is limited to classifying equivalence based on type, and has not yet done furhter analysis on wether the equivalence is classified as formal, dynamic, and equivalene in term of context. The result showed that 49% of the translations include equivalence at word level, 19% equivalence above word level, 19% grammatical equivalence, 13 % pragmatic equivalence, and 6% textual equivalence.